A tempest at sea [large type] - Thomas, Sherry (Sherry M.) (Thomas, Sherry (Sherry M.). Lady Sherlock series., 2023)
"Charlotte Holmes's brilliant mind and deductive skills are pulled into a dangerous investigation at sea in the new mystery in the bestselling Lady Sherlock series. After feigning her own death in Cornwall to escape from Moriarty's perilous attention, Charlotte Holmes goes into hiding. But then she receives a tempting offer: Find a dossier the crown is desperately seeking, and she might be able to go back to a normal life. Her search leads her aboard the RMS Provence. But on the night Charlotte makes her move to retrieve the dossier, in the midst of a terrifying storm in the Bay of Biscay, a brutal murder takes place on the ship. Instead of solving the crime, as she is accustomed to doing, Charlotte must take care not to be embroiled in this investigation, lest it become known to those who harbor ill intentions that Sherlock Holmes is abroad and still very much alive" --